Human Monkeypox Outbreaks from 2001 to 2021 – A Systematic Review - Yasir Akbar Jamali, Jawad Ahmad Khan, Wali Muhammad Mangrio, Abdul Majid, Shakil Ahmed Shaikh, Salma Farrukh Memon, Nadia Shaikh, Majid Ali Maitlo, Rabail Ghumro, Sadam Hussain Shaikh (Pakistan Journal of Medical & Health Sciences, 2022)
Background:- An infectious disease induced by orthopoxviruses is known as monkeypox. In 1958, a viral outbreak in caged monkeys was first identified as monkeypox. The Democratic Republic of Congo was the first country to record human cases in 1970. Methods:- We searched MEDLINE, Google Scholar, Web of science, African Journals Online, Embase, and public health and infectious diseases medical journals with phrases in the topic headings “human monkeypox”, “monkeypox”, and “human monkeypox outbreaks in Congo” for article published. Results:- A total number of 17 outbreaks from January 2001 to December 2021 were included in the review. Total suspected cases of human monkeypox were 2527 while 241 cases were confirmed by polymerase chain reaction (PCR) test. 29 deaths out of 2527 were reported in 17 outbreaks. Conclusion:- The Democratic Republic of the Congo was the site of the majority of outbreaks. Although the immunization vaccine can protect humans against monkeypox virus infection.